Pengaruh Media Video Animasi Berbasis Powtoon Terhadap Apresiasi Bercerita pada Siswa Sekolah Dasar - Haslinda; Harianto, Oki; Wahid, Abdul (Jurnal Pendidikan dan Pengajaran, 2024)
Storytelling in elementary education often faces challenges in engaging students and enhancing their appreciation. Innovative teaching media can address these issues effectively. This study aims to analyze  the impact of Powtoon-based animated video media on students' appreciation of storytelling in a third-grade classroom at SD. The research employed a one-group pretest-posttest experimental design, involving 27 students aged 11 to 12 years across 12 learning sessions. Data were collected using pretests and posttests, and were analyzed through data management, statistical analysis, and result interpretation. The results showed a significant increase in the average score from 52.03 on the pretest to 79.44 on the posttest following the Powtoon intervention. Inferential analysis using a t-test revealed a significant difference with a t-value of -8.859 and a critical t-value of 1.705 at a 5% significance level, supporting the acceptance of the alternative hypothesis that Powtoon has a positive effect on students' storytelling appreciation. These findings suggest that Powtoon has potential as an effective educational media for enhancing students' interest and skills in storytelling, thereby supporting the use of technology in education to create a more engaging learning environment.